Operational excellence in pharmaceuticals – a process based Approach in pantoprazole sodium ec pellets 20% w/w (pfi) By using managerial techniques - VENKATESWARA REDDY BOYA; DR.K. S. SEKHARA RAO (International Journal of Pharma and Bio Sciences, 2018)
The purpose of this research was carried out to prove the Operational Excellence on Pharmaceutical Formulation Intermediate (PFI) Pantoprazole Sodium EC Pellets 20% w/w by using managerial techniques. This study was carried out on antiulcer drugs, as majority of people are suffering from ulcer worldwide. This inspired me to take up the research on anti-ulcer drugs which benefits largely to cure ulcers. One of the molecules Pantoprazole is, Proton Pump Inhibitor (PPI) which decreases acid secretion from parietal cells present in the stomach. Pantoprazole is widely available and used medicine for ulcers. Three trials have been formulated for each of F1, F2 & F3 on Pantoprazole Sodium Enteric Coated Pellets 20% w/w by using managerial techniques such as time, men, material management with operational variants of HPMC-E5 (Film forming polymer), SLS (Surfactant) and Methacrylic acid co-polymer (L-30D) (Enteric polymer) and subjected for testing as per USP-40.20 All samples of F1, F2 & F3 obtained have been given acceptable results. Out of the three formulations, F3 formulation has been considered as a final processing formula and was validated. F3 samples have been found better results and projected yields. Acid dissolution: 1.6%, Buffer dissolution: 98.2%, Assay: 99.73% and Yield 97.7%. In the process of conducting these experiments utilities like power, HVAC, compressed air and equipment have been effectively used.